2022
DOI: 10.31223/x5kw3s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cascadia megathrust earthquake rupture model constrained by geodetic fault locking

Abstract: Paleo-earthquakes along the Cascadia subduction zone inferred from offshore sediments and Japan coastal tsunami deposits approximated to M9+ and ruptured the entire margin. However, due to the lack of modern megathrust earthquake records and generally quiescence of subduction fault seismicity, the potential megathrust rupture scenario and influence of downdip limit of the seismogenic zone are still obscure. In this study we present a numerical simulation of Cascadia subduction zone earthquake sequences in the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…In our models, we map the measured a‐b values of each unit to the temperature‐depth range over which it is inferred to have deformed (Figure 3c), following the approach of slow slip cycle continuum models (e.g., Liu & Rice, 2007). While our distribution of friction parameters is based directly on laboratory friction experiments coupled with microstructural and geothermometric analyses of the exhumed fault rock sequence, we note that the resulting frictional stability profile mirrors inferred interseismic locking patterns on the Mai'iu fault and thus accords with seismic cycle models that constrain fault friction based on geodetic inferences of interseismic coupling (e.g., Barbot et al., 2012; Li & Liu, 2021).…”
Section: Methodssupporting
confidence: 67%
“…In our models, we map the measured a‐b values of each unit to the temperature‐depth range over which it is inferred to have deformed (Figure 3c), following the approach of slow slip cycle continuum models (e.g., Liu & Rice, 2007). While our distribution of friction parameters is based directly on laboratory friction experiments coupled with microstructural and geothermometric analyses of the exhumed fault rock sequence, we note that the resulting frictional stability profile mirrors inferred interseismic locking patterns on the Mai'iu fault and thus accords with seismic cycle models that constrain fault friction based on geodetic inferences of interseismic coupling (e.g., Barbot et al., 2012; Li & Liu, 2021).…”
Section: Methodssupporting
confidence: 67%
“…It would be particularly valuable if information about the interseismic uplift‐rate could be constrained offshore, to extend existing onshore leveling data (Krogstad et al., 2016). This would reduce the ambiguity in geodetic coupling models and improve our understanding of the spatial relationships between upper plate deformation and intra‐plate slip behaviors (Bruhat & Segall, 2017; Li & Liu, 2021; Malatesta et al., 2021; Watt & Brothers, 2020). Our study stresses the importance of the spatial variation in coupling, especially in the central Cascadia region where confirming the presence of lower coupling offshore Oregon is critical for both kinematic and dynamic rupture simulation results.…”
Section: Discussionmentioning
confidence: 99%
“…The first order features of viscoelastic coupling models (e.g., Li et al., 2018; Yousefi et al., 2020) are not drastically different from the Gamma slip deficit rate distribution. Moreover, Li and Liu (2021) found that the Schmalzle et al. (2014) coupling models, when incorporated into quasi‐dynamic earthquake simulations, provide a stronger fit to the 1700 A.D. surface measurements.…”
Section: Introductionmentioning
confidence: 99%
“…With the main keyword ‘fracture dynamics', this theme issue covers diverse subjects, extending from theoretical yet significantly important model analyses, such as J. D. Eshelby-based [14] collective treatment of damage evolution in brittle materials [3], to practical safety and environmental problems associated with mining or rock excavation engineering, including the fundamental study on the brand-new contactless rock drilling technique using thermal shock [4]. As stated earlier, the scale treated is also diverse, ranging from a fracture at the atomic or microscopic level [2] to largely macroscopic rock/strain bursts or sudden collapse of stopes in deep underground gold mines [9], field observation-based reliable physical estimation of earthquake source parameters [8] or even to megathrust rupture (fracture) near tectonic boundaries of the earth [11]. The theme issue also handles front-line topics like fracture asperity development during the change between stick-slip and stable sliding [5], fracture-induced gravitational perturbations that propagate at the speed of light [12] and seismic events induced by human activity like a fluid injection that can become concerns of the residents nearby [6].…”
Section: Summary Of the Theme Issuementioning
confidence: 99%
“…The numerical examples they treat range from the co-seismic generation of secondary off-fault shear cracks to the natural convection in molten rock-like solid. By taking into account a sophisticated rate- and state-dependent friction law with the parameters constrained by geodetic fault locking, Li & Liu [11] develop a three-dimensional megathrust earthquake cycle model for the Cascadia subduction zone that may cause a seismic event with a magnitude over 9. They present a numerical simulation of earthquake sequences and evaluate potential seismic risks.…”
Section: Summary Of the Theme Issuementioning
confidence: 99%